Propeller/rudder interaction with direct and coupled CFD/potential flow propeller approaches, and application to a zigzag manoeuvre. Issue 1 (2nd January 2018) - Mofidi, Alireza; Martin, J. Ezequiel; Carrica, Pablo M.
ABSTRACT: This paper investigates a coupled computational fluid dynamics (CFD)/potential propeller code approach to simulate maneuvers of ships. While this approach is successful in submarines, the concept has not been evaluated before for cases where an object (the rudder) is immersed in the wake. The study uses the CFD code REX and the propeller code PUF-14 applied to propeller/rudder interactions in open water configuration and to a 15/1 zigzag maneuver for the KCS container ship. Self-propulsion results, and motions, forces, moments and mean flow field during the maneuver agree well with experiments and discretized propeller simulations. The approach is an effective and economical way to perform direct simulation of surface ship maneuvers, providing CPU time savings approaching an order of magnitude. Massively separated rudder flows may not perform as well, since the propeller turbulence reaching the rudder is under-predicted in the coupled approach.